2020
DOI: 10.1111/jch.14060
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of hypertension prevalence based on 2017 ACC/AHA and 2018 Chinese hypertension guidelines: Results from CHNS data (1991‐2015)

Abstract: This study aimed to assess the impact of the 2017 American College of Cardiology and American Heart Association (ACC/AHA) guideline and the 2018 Chinese hypertension guidelines on the different secular trends for hypertension prevalence. A total of 82 665 eligible individuals aged ≥20 years were selected from nine cross‐sectional study periods (1991‐2015) from the China Health and Nutrition Survey (CHNS). Over the 24‐year period, the long‐term trend for the prevalence of the 2017 ACC/AHA‐defined age‐adjusted h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Multiple cross‐sectional and cohort studies have also confirmed the relationship between hypertension and the occurrence and progression of clinical symptoms of AD, demonstrating that hypertension was also common in patients with AD 29–31 . Interventions that normalize blood pressure and promote microvascular health may prevent cognitive decline during old age 32 …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Multiple cross‐sectional and cohort studies have also confirmed the relationship between hypertension and the occurrence and progression of clinical symptoms of AD, demonstrating that hypertension was also common in patients with AD 29–31 . Interventions that normalize blood pressure and promote microvascular health may prevent cognitive decline during old age 32 …”
Section: Introductionmentioning
confidence: 92%
“…[29][30][31] Interventions that normalize blood pressure and promote microvascular health may prevent cognitive decline during old age. 32 In this study, hypertension and diabetes were identified as the main causes of cognitive impairment. In addition, older people are more susceptible to stress, depression, and sleep deprivation, which also contribute to the development of AD and other types of dementia.…”
Section: Introductionmentioning
confidence: 93%
“…Meanwhile, we found in this study that the prevalence of hypertension increased more than doubled from 13.11% in 1993 to 32.14% in 2015. Other studies in China also revealed the high increase of prevalence of hypertension [ 30 , 31 ]. However, it is estimated that the prevalence would grow 55% by year 2050 if no interventions on hypertension control are taken [ 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…In Tehran 22 , Yazd 23 , and Khuzestan 24 , hypertension prevalence was estimated to change from 20.4-47.1%, 28.9-61.0%, and dramatically from 15.81-42.85% with ACC/AHA adoption instead of JNC7. Internationally, adopting the ACC/AHA guideline in China doubled hypertension prevalence 25 , and also showed a steeper trend, while Brazil experienced a 2.6-fold increase, from 21.1-54.7% 26 . In Bangladesh, JNC7 and 2017 ACC/AHA classi ed 25.7% and 48.0% of the population as having hypertension, respectively 27 .…”
Section: Discussionmentioning
confidence: 99%